2004
DOI: 10.1002/jcp.20140
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of embryologically distinct urothelial cells is inhibited by SPARC

Abstract: The AON epitope of secreted protein acidic and rich in cysteine (SPARC) is a conserved motif expressed by human SPARC in a variety of human cell types. Through the use of a monoclonal antibody that recognizes this epitope, transitional epithelium was found to restrict expression of SPARC to the suprabasal and intermediate layer. Such intracellular expression was defined by immunoreactive signals that localized to the apical plasma membranes of suprabasal and intermediate cells. Polarization of SPARC to apical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 49 publications
1
30
0
2
Order By: Relevance
“…How urothelial cells spread is central to understanding a number of bladder diseases. The extracellular matrix-associated secreted protein acidic and rich in cysteine (SPARC), also known as BM-40 and osteonectin (Termine et al, 1981;Romberg et al, 1985), has been shown to inhibit the spreading of human urothelial cells derived from embryologically distinct origins in concentration-and time-dependent processes (Hudson et al, 2005). Such inhibitory activity provides a mechanism in which SPARC can modulate the interactions between basal urothelial cells and the urothelial basement membrane.…”
Section: þmentioning
confidence: 99%
“…How urothelial cells spread is central to understanding a number of bladder diseases. The extracellular matrix-associated secreted protein acidic and rich in cysteine (SPARC), also known as BM-40 and osteonectin (Termine et al, 1981;Romberg et al, 1985), has been shown to inhibit the spreading of human urothelial cells derived from embryologically distinct origins in concentration-and time-dependent processes (Hudson et al, 2005). Such inhibitory activity provides a mechanism in which SPARC can modulate the interactions between basal urothelial cells and the urothelial basement membrane.…”
Section: þmentioning
confidence: 99%
“…SPARC is expressed in normal murine and human urothelia and suburothelial stroma (20) and in primary cultures of human urothelial cells (21)(22)(23). SPARC has been shown to exert an antiadhesive and antiproliferative effect on human and murine urothelial cells (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…A previous report [Gooden et al, 1999] has highlighted that SPARC localized to the nucleus during specific cell cycle phases. Moreover, Yan et al [2005] described a translocation of SPARC to the nucleus of lens epithelial cells and SPARC nuclear localization has also been observed in urothelial cells [Hudson et al, 2005]. In addition, it has been very recently demonstrated that recombinant SPARC can be internalized in the cell and be translocated to cell nucleus where it inhibits DNA synthesis [Kosman et al, 2007].…”
Section: Discussionmentioning
confidence: 96%
“…Cell Compartments of HOBIT Cells SPARC subcellular distribution is still debated, as some recent reports highlighted a nuclear staining for SPARC in human urothelial [Hudson et al, 2005] and immortalized murine lens epithelial cells [Yan et al, 2005], even though other studies demonstrated only a cytoplasmic localization. In several cell lines, intracellular SPARC has been co-localized to endoplasmic reticulum and Golgi complex, presumably destined for secretion [Lane and Sage, 1994], while Gooden et al [1999] presented evidence that the distribution of endogenous, intracellular SPARC can vary according to specific phases of the cell cycle.…”
Section: Sparc Is Detected In Nuclear and Cytoplasmicmentioning
confidence: 99%
See 1 more Smart Citation